Teun A. van Dijk's Critical Discourse Analysis Model of The Premediated Murder Case of Brig. Joshua Hutabarat by Suspended Internal Affairs Chief Insp. Gen Ferdy Sambo Reported on the Online Media Kompas.com - Syaffiatu Lutfiana; Sri Utami; Agus Hermawan; Lailiyatus Sa'diyah (Journal of Development Research, 2023)
The Premediated murder case that was carried out by the Suspended Internal Affairs Chief Insp. Gen Ferdy Sambo on Brigadier Joshua, became the most prominent case that occurred in the mid-2022 to early 2023. This phenomenon attracted the Indonesian people’s apprehension, especially as the murder occurred in a police agency. This research aimed to analyze text structure, social cognition, and social context on the online media Kompas.com regarding the case of the Premediated murder case of Brigadier Joshua by Ferdy Sambo. The research data sources were five news taken from the mass media Kompas.com. This research was qualitative descriptive research with data collection techniques through documentation. Data analysis techniques in this research included data reduction, data presentation, and drawing conclusions. The results of this research found that five news portals had the same theme and topic, that were informing about the murder case of Brigadier Joshua by Ferdy Sambo. The five news stories met the level of discourse analysis using Teun A. van Djik's model, namely: (1) text structure (a. macrostructure; b. superstructure; c. microstructure); (2) social cognition; and (3) social context. Especially, at the microstructure level which is part of the text structure, it does not meet the criteria in discourse analysis because there are no presupposition and metaphor elements. The five online news stories published by Kompas.com regarding this case correspond to actual conditions in the field. This research has implications for specific moral values for readers to be more selective in choosing news portals.